Gulo gulo Pallas 1780 - Wilson, Don E.; Mittermeier, Russell A. (Zenodo, 2009)
8. Wolverine Gulo gulo French: Carcajou / German: Vielfrafls / Spanish: Gloton Taxonomy. Mustela gulo Linnaeus, 1758, Lapland. Two subspecies are recognized. Subspecies and Distribution. G. g. gulo Linnaeus, 1758 — NE & NW China, Mongolia, Russia, and Scandinavia. G. g. luscus Linnaeus, 1758 — Canada and W USA (Alaska, California, Idaho, Oregon, Montana, Washington & Wyoming). Descriptive notes. Head-body 65-105 cm, tail 21-26 cm; weight 11-18 kg (males), 6-12 kg (females), adult males are larger and heavier than females. The Wolverine is heavily built and stocky, and is the largest terrestrial member of the Mustelidae. The pelage is long and varies in color from almost blond to dark brown, with two distinctive yellowish stripes that run from the top of the neck to the rump. White patches on the throat, belly or limbs are common. The head is large, with a broad forehead, broad nose, and rounded ears. The limbs are relatively short and the tail is bushy. The feet are large, with well-developed claws. The skull is exceptionally robust and broad, with a well-developed sagittal crest. Dental formula: 13/3, C 1/1, P 4/4, M 1/2 = 38. The teeth are big and strong; the carnassials are very large. Habitat. Wolverines are found in mature conifer forests in the taiga and in the treeless tundra. They are inhabitants of remote northern areas where there are few humans. Wolverines make greater use of forested areas during winter, and greater use of tundra during summer. Altitudinal movements may also occur seasonally, with higher elevations being occupied during the summer and lower altitudes during the winter, probably because of snow accumulation and prey abundance. In central Idaho, USA, radiotracked Wolverines used higher elevations in summer versus winter, and they shifted use of cover types from whitebark pine (Pinus albicaulis) in summer to lower elevation Douglas-fir (Pseudotsuga menziezii) and lodgepole pine (Pinus contorta) communities in winter. Wolverines also preferred northerly aspects, but avoided roads and ungulate winter range. In British Columbia, Canada, radio-telemetry revealed that Wolverines negatively responded to human disturbance within occupied habitat; males tended to avoid helicopter skiing areas. Habitat associations of females were more complex, but in the summer they avoided roads and recently logged areas. In the Columbia Mountains, where winter recreation is widespread, females prefer alpine and avalanche environments where Hoary Marmot (Marmota caligata) and Columbia Ground Squirrel prey are found in the summer. During the winter, females tend to avoid areas with helicopter and backcountry skiing, and prefer areas where Moose (Alces alces) can be found. Food and Feeding. The diet includes the carcasses of large ungulates, such as Moose and Reindeer (Rangifer tarandus). In many areas, Wolverines are dependent on the ability of larger predators, especially Gray Wolves, to provide kills. In coastal areas, they also feed on the carcasses of whales and seals that wash ashore. Wolverines also prey opportunistically on deer, sheep, small mammals (rodents such as Marmota and Myodes, lagomorphs, and ground squirrels), birds, and eggs. Berries, nuts and fungus are occasionally eaten. Within two study areas in British Columbia, scat analysis revealed a diet that varied regionally and seasonally: Moose, Reindeer, and Hoary Marmots were abundant and common prey items within both study areas. Mountain Goats (Oreamnos americanus) and North American Porcupine (Erithizon dorsata) were more frequent prey items in the Columbia Mountains, while Snowshoe Hare (Lepus americanus) and American Beaver (Castor canadensis) were more frequent prey items in the Omineca Mountains. Reindeer, Hoary Marmots, and North American Porcupines were found in significantly higher frequencies in the diet of reproductive females. Predation on ungulates (such as Reindeer)is facilitated when there is deep snow. Wolverines kill larger prey by a bite at the neck or throat. Small rodents may be chased, pounced upon, or dug out of the ground. Excess food is cached for later use and is covered with earth or snow, or sometimes wedged in the forks of trees. In Alberta and British Columbia, cache sites were in stands of black spruce (Picea mariana) or mixed-wood of high complexity, dominated by conifers, and in which the trembling aspen (Populus tremuloides) and balsam poplar (Populus balsamifera) component consisted of mostly dead or dying trees. These sites offered relatively good visibility of the surrounding area; caches were never located in the very dense homogenous spruce stands. Cache sites were classified as “simple caches”, composed of a single feeding site and/or excavation, and “cache complexes”, involving one or more feeding “stations”, latrines, resting sites, and climbing trees that may have been used as avenues of escape from competitors or predators. The better used cache complexes were accessed by numerous well-used trails made by the Wolverines themselves. Caches contained the remains of Moose that were believed to have been killed by Wolves. Activity patterns. Mainly nocturnal, but occasionally active during the day. Rest sites may be a rough bed of grass or leaves in a cave or rock crevice, in a burrow made by another animal, or under a fallen tree. In Alberta and British Columbia, resting sites were located on top of the snow in relatively open locations that offered good visibility of the surroundings. Wolverines do not appear to be hindered by deep snow and are active year round. Movements, Home range and Social organization. Wolverines are solitary and mainly terrestrial, but are also strong swimmers and agile tree climbers. Their scavenging habits dictate covering long distances. Daily movements in excess of 30 km are common; males travel more widely than females. They are capable of reaching speeds of 45 km /h. In north-western Alaska, the home ranges of males were 488-917 km * and 53-232 km? for females. In south-central Alaska, home ranges averaged 535 km ” for males and 105 km? for females. In Yukon, home ranges were 209-269 km * for males and 76-269 km? for females. The home range of each male overlaps three or four females. However, in Montana, there was extensive overlap between the ranges of both the same and opposite sexes, and no territorial defense was observed. Population densities vary from one animal per 50 km? in Siberia to one per 500 km * in Scandinavia. North American densities vary from one per 65 km? to one per 200 km. Breeding. Wolverines exhibit a polygamous mating system, as some males produce offspring with more than one female in a single year. Females often reproduce with the same male in subsequent breeding years, but sometimes change their partner, possibly as a consequence of a change in the territory-holding male in the area. Females are monoestrous and apparently give birth about every two years. Mating occurs from May to August. Ovulation is induced; implantation of the fertilized eggs into the uterus is delayed until the following November to March. Births occur from January to April, after a total gestation period of 215-270 days. Maternal dens are located in alpine, subalpine, taiga, or tundra habitat; reports of dens in low elevation, densely forested habitats are rare. Dens in Alaska are usually long, complex snow tunnels with no associated trees or boulders. In Idaho, dens are associated with fallen trees or boulders. In both areas, all dens are covered with at least 1 m of snow. Litter size is one to five; usually two to four. The young weigh about 84 g at birth and are born fully furred, but with their eyes closed. Weaning occurs after seven to eight weeks, and adultsize is reached by November, when the young separate from the mother. Females raise the young alone. Sexual maturity is attained after two or three years. Status and Conservation. Classified as Near Threatened in The IUCN Red Listt. Wolverines are harvested for their pelt; although their fur is not used widely in commerce it is valued for parkas. Fur trapping has contributed to a decline in numbers and distribution of the Wolverine. Wolverines are also intensely hunted because they are considered a nuisance animal: they follow traplines and devour trapped furbearers, they break into cabins and food caches, they allegedly prey on domestic reindeer, and they attack sheep. Protection and recovery measures are needed to restore populations acrossits previously known range. Bibliography. Aubry et al. (2007), Banci & Harestad (1988), Copeland & Whitman (2003), Copeland et al. (2007), Hedmark et al. (2007), Hornocker & Hash (1981), Krebs et al. (2007), Krott (1960), Landa, Linden & Kojola (2000), Landa, Strand, Linnell & Skogland (1998), Landa, Strand, Swenson & Skogland (1997), Lofroth et al. (2007), Magoun & Copeland (1998), Mead et al. (1991), Pasitschniak-Arts & Lariviere (1995), Stroganov (1969), Whitman et al. (1986), Wozencraft (2005, 2008), Wright & Ernst (2004a, 2004b). : Published as part of Don E. Wilson & Russell A. Mittermeier, 2009, Mustelidae, pp. 564-656 in Handbook of the Mammals of the World – Volume 1 Carnivores, Barcelona :Lynx Edicions on pages 627-628, DOI: 10.5281/zenodo.5714044